Psychometric Properties from Geriatric Social Work Competencies Scale II - Rubio A. Suarez (GoAcademica Research & Publishing, 2020)
The Geriatric Social Work Competencies Scale II (GSWCS II) is considered a reference in the assessment of the competencies of Gero Social Workers. The aim of the study is to examine the psychometric properties of GSWCS II in a sample of Portuguese social workers work-ing with elderly people. The GSWCS II was administered in conjunction with a specific designed socio-professional questionnaire. A total of 543 social workers were interviewed, with a mean age of 33.05 (7.57 = SD), female (96.1%) and in management functions (72.5%). Internal consistency was verified with high values ​​in all dimensions (α > 9). The scale has high cor-relations with all its dimensions (> 85). The Confirmatory Factor Analysis was used to test the model, based on a five-dimensional structure, the chi-square test of adjustment (χ2/df) = 3.129 presented an acceptable index of adjustment. The GSWCS II proved to be a valid and reliable scale for this population.